(untitled) (Journal of Mathematical Study, 2023)
In this paper, we consider the global dynamics of the Cahn-Hilliard/Allen-Cahn equation with periodic boundary value conditions in 2D bounded domain Ω. We show that the equation has a global attractor in H^4_per(Ω) when the initial value belongs to H^1_per(Ω).